Persuasive Strategies in Donald Trump's Political Speeches - Wilma Prafitri; Muhammad Alim Akbar Nasir (The Study Program of English Education of Palangka Raya University, 2023)
This study analyses persuasive strategies on Donald Trump’s political speeches. This study uses qualitative research as the design and Content Analysis as the approach. The researcher explores persuasive strategies used by Donald Trump using Aristotle’s Theory to see what persuasive strategies are used and how Trump’s political speech could affect audiences to vote for him. The researcher selected three speeches such as campaign speech (2015),victory speech (2016) and inauguration speech (2017) as the object of study. These speeches are selected based on some considerations, such as lexical density, political concepts described by Trump, academic scrutiny and also to make this research more manageable. Furthermore, the researcher found that Trump has used persuasive strategies in order to convince Americans to vote him as President. According to Aristotle , there are three types of Persuasive Strategies such as Logos, Ethos and Pathos. The researcher found thirty one statements indicated of containing pathos, thirteen statements of Logos and fifteen statements as Ethos. Pathos encompasses the emotional influence on the audience. Based on the analysis, the researcher concludes that persuasive strategies played crucial part to evoke audience’s emotions and feelings.